TINJAUAN KOMPILASI HUKUM ISLAM DAN HUKUM POSITIF INDONESIA TERHADAP DAMPAK BEKERJA DI LUAR NEGERI BAGI KEHARMONISAN RUMAH TANGGA - Nurhidayati, Nurhidayati; Rahmadani, Ezmi Sivana (Institut Agama Islam Negeri Metro, 2022)
The lack of employment opportunities makes the number of unemployed continue to increase, people are unable to start a business due to limited capital, expertise, and market access. Moreover, there are many positive benefits for migrant workers who work abroad to get jobs, income, improve welfare and improve skills. When the government programs this program plans to limit unemployment in the country, expand job opportunities and increase income from foreign exchange. This research uses qualitative research procedures. The results of the discussion in this study are that there are several impacts of working abroad, the first being negative impacts, violence at work and frequent divorces in the household; and positive impact, reducing unemployment and establishing relations between countries. There are some especially TKI who but have an understanding of education graduates from elementary school (elementary school) and junior high school (junior high school), in fact there are also high school graduates (high school). As for the people who do not have skills and only limited education can get sufficient income without thinking about the negative impact.